The BERA/SAGE handbook of educational research - Wyse, Dominic 1964-; Selwyn, Neil; Smith, Emma (Professor); Suter, Larry; British Educational Research Association (Los Angeles, California Sage Reference, 2017)
The British Educational Research Association (BERA) has worked with SAGE to develop a high quality research methods handbook for students studying education and related areas. The book is published in two volumes and over 1,000 pages. The contributions are listed thematically in six parts, progressing from a background to research enquiry, through planning research, approaches or design, acquiring data, analysis and lastly reporting, disseminating and evaluation. Over 50 authors are included, many highly eminent in their fields. This handbook makes a valuable and authoritative contribution to the research endeavour for all those working or studying in the field of education. [Publisher website, ed].
Introduction -- Part 01: Understanding research / Ian Menter. Reasons for education research / Mary Lou Rasmussen -- The role of theory in research / Hannah Farrimond -- The ethics of research / Sean Kelly -- Shared principles of causal inference in qualitative and quantitative research / Joseph A. Maxwell -- The validity and reliability of research: a realist perspective -- Part 02: Planning research / Jill Denner, Erica Marsh & Shannon Campe -- Approaches to Reviewing Research in Education / Peter Tymms -- Purposes for Educational Research / Patrick White -- Research questions in education research: their neglect, role and development / Stephen Gorard -- An introduction to the importance of research design / Roger Gomm -- A positivist orientation: hypothesis testing and the 'scientific method' / David Scott -- Interpretivism as a theory of knowledge / R. Burke Johnson, Anthony J. Onwuegbuzie, Cornelis de Waal, Tres Stefurak & David Hildebrand -- Unpacking pragmatism for mixed methods research: the philosophies of Peirce, James, Dewey, and Rorty / Kathleen Collins -- Sampling decisions in educational research: criteria, designs, challenges -- Part 03: Approaches to research / Gary McCulloch -- Historical research / Larry E. Suter. Using International Comparative Studies in Achievement in Educational Research -- Sara Delamont -- Ethnography / Robert Thornberg -- Grounded Theory / Malcolm Tight -- Case Study Research / Alice Sullivan & Lisa Calderwood -- Surveys: longitudinal, cross-sectional and trend studies / Carole J. Torgerson & David J. Torgerson -- True Experimental designs / Mary Brydon-Miller, Maricar Prudente & Socorro Aguja -- Lighting a spark, seeing the light: educational action research as transformative practice / Sandy Oliver & Janice Tripney -- Systematic review and meta-analysis / Pamela Sammons & Susila Davis -- Mixed methods approaches and their application in educational research / Pamela E. Davis-Kean & Justin Jager -- Using secondary data analysis for educational research / Rebecca Eynon -- Researching in digital environments -- Part 04: Acquiring data / Jerry West -- Access, Sites and Settings / Frank Hardman & Jan Hardman -- Observation and recording classroom processes / Amanda Berry & Monica Taylor -- Personal experience methods in practitioner research / Mark Nelson. Multimodality, meaning and data analysis / Amir Marvasti & Carrie Freie. Research interviews / Stacey Bielick -- Surveys and questionnaires / Stephen G. Sireci and Joshua Marland -- Measurement / Part 05: Analysing data / Susan Jekielek -- Cataloguing and organizing data / Terri D. Pigott -- The role of theory in quantitative data analysis / Jeffrey T. Steedle. Descriptive statistics -- Paul E. Jose & Agnes Szabo -- Inferential statistics / Stephen Gorard -- How should numeric data be analysed? / Barbara B. Kawulich -- Coding and analyzing qualitative data / Myrte Gosen & Tom Koole -- Conversation Analysis / Christoph A. Hafner -- Discourse analysis -- Critical discourse analysis / James B. Schreiber & Lyndsie N. Ferrara -- Content Analysis / Betsy McCoach and Sarah D. Newton -- Confirmatory Factor Analysis / Chao-Ying Joanne Peng -- Logistic Regression -- Harvey Goldstein -- Multilevel modelling for educational data / Roser Beneito-Montagut -- Big Data and Educational Research -- Part 06: Reporting, Disseminating & evaluating research / Guillermo Solano-Flores -- Generalizability / Pat Thomson -- Writing about research / Mark Rickinson -- Communicating Research Findings / Inger Mewburn & Pat Thomson -- Social media and academic publishing / Larry E. Suter -- Evaluation of and accountability for individual and institutional research on education / Chris Brown -- Using research findings.
Published jointly with BERA, British Educational Research Association.
Includes bibliographical references and index.
Keywords: Education -- Research -- Handbooks, manuals, etc; Education -- Research -- Methodology -- Handbooks, manuals, etc